Pulsed ultraviolet light processing for microbial inactivation and its applications for food and water safety - Uslu, Gulsad; Demirci, Ali (CRC Press, 2016)
[Abstract Not Available]
Keywords: ITS applications; Microbial inactivation; Pulsed ultraviolet lights; Water safety